Profil Malaria pada Remaja di Kota Bitung Periode Juli – November 2023 - Firra, Andi H. F.; Tuda, Josef S. B.; Pijoh, Victor D. (e-CliniC, 2025)
Abstract: In North Sulawesi, malaria remains as a significant health issue, indicated by the high number of clinical cases and positive results in several areas. Bitung City is an area with sandy soil and is directly adjacent to the coastline, with a high population density. Residing in a malaria-endemic area makes the population of Bitung City vulnerable to malaria, especially teenager who are in the explorative age group. This study aimed to determine the profile of malaria among teenagers in Bitung City during the period of July to November 2023. This was a descriptive study with a cross-sectional approach. The data obtained were organized in the form of frequency distribution tables, and discussed according to malaria agents and the respondents’ gender. The results showed that there were more male respondents than females (59%:41%). The most frequent type of malaria agent was Plasmodium vivax (49%), and less in Plasmodium falciparum (6%); none in Plasmodium ovale and Plasmodium malariae (0%). In conclusion, the dominant malaria parasite species among teenagers in Bitung was Plasmodium vivax. There are more male teenagers suffering from malaria than female teenagers. Keywords: Plasmodium; malaria; teenagers; gender    Abstrak: Di Sulawesi Utara malaria masih menjadi permasalahan kesehatan yang ditunjukkan oleh tingginya jumlah kasus klinis dan hasil positif pada beberapa daerah. Kota Bitung ialah wilayah dengan tanah berpasir dan berbatasan langsung dengan garis pantai yang memiliki kepadatan penduduk tinggi. Berdiam di wilayah endemik malaria membuat penduduk Kota Bitung rentan terhadap malaria, khususnya usia remaja yang merupakan usia eksploratif. Penelitian ini bertujuan untuk mengetahui profil malaria pada remaja di Kota Bitung periode Juli – November 2023. Jenis penelitian ini ialah deskriptif dengan desain potong lintang. Data perolehan disusun dalam bentuk tabel distribusi frekuensi, dan dibahas menurut agen malaria dan jenis kelamin responden. Hasil penelitian mendapatkan jenis kelamin responden paling banyak ialah laki-laki (59%), lebih sedikit pada perempuan (41%). Jenis agen malaria responden paling banyak ialah Plasmodium vivax (49%), sedikit pada Plasmodium falciparum (6%), dan tidak ada pada Plasmodium ovale dan Plasmodium malariae (0%). Simpulan penelitian ini ialah spesies parasit malaria yang dominan di Bitung ialah Plasmodium vivax. Penderita malaria didapatkan lebih banyak pada remaja laki-laki dibandingkan remaja perempuan. Kata kunci: plasmodium; malaria; remaja; jenis kelamin